Cytokine Networking in Lungs of Immunocompetent Mice in Response to Inhaled Aspergillus fumigatus - Brieland, Joan K. (American Society for Microbiology, 2001)
Cytokine networking in the lung in response to inhaled Aspergillus fumigatus was assessed using a murine model of primary pulmonary aspergillosis in immunocompetent Crl:CF-1 mice. Inhalation of virulent A. fumigatus (6 × 10(6) CFU) resulted in the induction of interleukin 18 (IL-18), tumor necrosis factor alpha (TNF-α), IL-12, and gamma interferon (IFN-γ) protein in bronchoalveolar lavage fluid and/or lung tissue. Induction of immunoreactive IL-18 preceded induction of TNF-α protein, which preceded induction of immunoreactive IL-12 and IFN-γ. Real-time reverse transcriptase (RT) PCR analysis of infected lung tissue demonstrated that induction of IL-18 protein also preceded induction of pulmonary TNF-α, IL-12, and IFN-γ mRNAs. Mice were subsequently treated with cytokine-specific neutralizing monoclonal antibodies (MAbs) to the IL-18 receptor (anti-IL-18R MAb), TNF-α (anti-TNF-α MAb), IL-12 (anti-IL-12 MAb), and/or IFN-γ (anti-IFN-γ MAb), and effects on intrapulmonary cytokine activity and growth of A. fumigatus were assessed in infected lung homogenates. Simultaneous neutralization of IL-12 and IL-18 resulted in decreased levels of immunoreactive TNF-α, while neutralization of IL-18, TNF-α, or IL-12 alone or of IL-18 and IL-12 together resulted in decreased levels of immunoreactive IFN-γ. Simultaneous neutralization of IL-12 and IL-18 or neutralization of TNF-α alone or in combination with IL-12, IL-18, or IFN-γ also resulted in a significant increase in A. fumigatus CFU in lung tissue. Taken together, these results demonstrate that endogenous IL-18, IL-12, and TNF-α, through their modulatory effects on both intrapulmonary cytokine activity and growth of A. fumigatus, play key roles in host defense against primary pulmonary aspergillosis.